Beach Morphology Changes Due to Sediment Transport Generated by Wave and Current in The Sea Waters of Bengkulu City, Indonesia - Supiyati Supiyati; Suwarsono Suwarsono; Mhd Ikhwanuddin Abdullah; Ichsan Setiawan (Marine Science Department Diponegoro University, 2022)
Bengkulu City which is located on the west coast of Sumatra Island has a very prospective to be developed for marine, fisheries, tourism, and maritime businesses. However, the coast of Bengkulu has recently changed in its morphology as a result of high sedimentation processes. The purpose of this study is to determine the direction and speed of currents, waves, and sediment transport that cause the changes in the coastal morphology of Bengkulu City. In this study, numerical modeling and field measurements of the current velocity and wave height of the ocean were used. The results of the research show verification of wave height and velocity of ocean currents between model simulation and field measurement is a fairly good fit, with a Mean Absolute Percent Error (MAPE) of 1.5% for wave height and 1.9% for the current velocity. The hydrodynamic simulation shows that the direction of the waves and currents dominantly come from the West and move towards the Northeast of the coastal of Bengkulu City with an average wave height of 2.5 m and the highest wave height of 6.5 m, the lowest wave height of 0.5 m, and the highest and the lowest of current speed is 2.5 m.s-1 and is 0.5 m.s-1, respectively. The simulation of sediment transport shows that the overall net volume is sedimented at about 20.25 m3.y-1. The model of coastal morphology changes shows that the sedimentation occurs in the northeast direction of the coastal of Bengkulu City, from Sungai Hitam Beach to Tapak Paderi Beach, and at Pulau Baai Beach.